An Aluminum Telluride with a Terminal Al=Te Bond and its Conversion to an Aluminum Tellurocarbonate by CO2 Reduction. (6th February 2023) - Xu, Huihui; Kostenko, Arseni; Weetman, Catherine; Fujimori, Shiori; Inoue, Shigeyoshi
Abstract: Facile access to dimeric heavier aluminum chalcogenides [(NHC)Al(Tipp)‐μ‐Ch]2 (NHC=I i Pr (1, 3‐diisopropyl‐4, 5‐dimethylimidazol‐2‐ylidene, IMe4 (1, 3, 4, 5‐tetramethylimidazol‐2‐ylidene); Tipp=2, 4, 6‐ i Pr3 C6 H2 ; Ch=Se, Te) by treatment of NHC‐stabilized aluminum dihydrides with elemental Se and Te is reported. The higher affinity of IMe4 in comparison with I i Pr toward the Al center in [(NHC)Al(Tipp)‐μ‐Ch]2 can be used for ligand exchange. Additionally, the presence of excess IMe4 allows for cleavage of the dimers to form a rare example of a neutral multiply bonded heavier aluminum chalcogenide in the form of a tetracoordinate aluminum complex, (IMe4 )2 (Tipp)Al=Te. This species reacts with three equivalents of CO2 across two Al−C NHC and the Al=Te bond affording a pentacoordinate aluminum complex containing a dianionic tellurocarbonate ligand [CO2 Te] 2−, which is the first example of tellurium analogue of a carbonate [CO3 ] 2− . Abstract : Facile isolation of various dimeric aluminum selenides and tellurides, as well as an aluminum‐telluride monomer featuring a terminal Al=Te bond, is reported. The aluminum‐telluride monomer exhibits high thermal stability and reacts with three equivalents of CO2 to form an unprecedented tellurocarbonate [CO2 Te] 2− substituted aluminum complex, which is the first example of tellurium analogue of the carbonate [CO3 ] 2− .